Same, same but different: symbiotic bacterial associations in GBR sponges - Webster, Nicole S.; Luter, Heidi M.; Soo, Rochelle M.; Botté, Emanuelle S.; Simister, Rachel L.; Abdo, Dave; Whalan, Steve (Frontiers in Microbiology, 2013)
Symbioses in marine sponges involve diverse consortia of microorganisms that contribute to the health and ecology of their hosts. The microbial communities of 13 taxonomically diverse Great Barrier Reef (GBR) sponge species were assessed by DGGE and 16S rRNA gene sequencing to determine intra and inter species variation in bacterial symbiont composition. Microbial profiling revealed communities that were largely conserved within different individuals of each species with intra species similarity ranging from 65-100%. 16S rRNA gene sequencing revealed that the communities were dominated by Proteobacteria, Chloroflexi, Acidobacteria, Actinobacteria, Nitrospira and Cyanobacteria. Sponge-associated microbes were also highly host-specific with no operational taxonomic units (OTUs) common to all species and the most ubiquitous OTU found in only 5 of the 13 sponge species. In total, 91% of the OTUs were restricted to a single sponge species. However, GBR sponge microbes were more closely related to other sponge-derived bacteria than they were to environmental communities with sequences falling within 50 of the 173 previously defined sponge-(or sponge-coral) specific sequence clusters. These sequence clusters spanned the Acidobacteria, Actinobacteria, Proteobacteria, Bacteroidetes, Chloroflexi, Cyanobacteria, Gemmatimonadetes, Nitrospira and the Planctomycetes-Verrucomicrobia-Chlamydiae superphylum. The number of sequences assigned to these sponge-specific clusters across all species ranged from 0% to 92%. No relationship between host phylogeny and symbiont communities were observed across the different sponge orders, although the highest level of similarity was detected in two closely related Xestospongia species. This study identifies the core microbial inhabitants in a range of GBR sponges thereby providing the basis for future studies on sponge symbiotic function and research aiming to predict how sponge holobionts will respond to environmental perturbation.